Selling Revolution: Advertisements, Marketing, and Network-Building in the Radical Press of 1970s France. - Miles, Sarah K. (French Politics, Culture & Society)
For left-wing revolutionary groups in 1970s France, to have a publication was to exist. In the face of a dramatic increase in the number of newspapers, magazines, and pamphlets, however, militant editors often struggled for survival as they attempted to build a base of reliable readers. In this context, economic viability and ideological influence were intertwined. This article examines the production and consumption of French leftist media in the 1970s to understand how revolutionary publications co-opted capitalist sales techniques in service of radical social and political goals. In couching the practices of capitalist media in the language of socialism, editors and readers built strong revolutionary communities while also, unintentionally, softening popular perceptions of certain market behaviors that breathed new life into French capitalism.